COMPARATIVE ANALYSIS OF PARTIAL EXTERNAL SHADING ON THE PERFORMANCE OF GREENHOUSE GROWN CUCUMBER {CUCUMIS SATIVUS) AND OKRA {ABELMOSCHUS ESCULENTUS) (2019)
Greenhouse cultivation is highly influenced by the microclimate, which affects plant growth and development. Shading is an option for ensuring a relatively cool environment within tropical greenhouses which tends to heat up due to intense solar radiations. This study was aimed at comparing the microclimate between a partially shaded greenhouse and an unshaded one with respect to its effect on the crops. Cucumber (Cucumis sativus) and okra (Abelmoschus esculentus) were grown in two greenhouses during the dry season of early 2018. One greenhouse was shaded with white coloured high-density polythelene film at the roof level while the other greenhouse was left unshaded. Both greenhouses were naturally ventilated. Results showed that shading had a positive effect on the okra growth compared to the okra parameters observed in the unshaded greenhouse as there was significant difference in the leaf length, leaf breadth, stem girth, plant height and yield (3.71± 0.58 and 2.56±1.21 t/ha for shaded and unshaded respectively) at P < 0.05. There was significant difference in stem height of cucumber, as well as the incoming solar radiation at P < 0.05. Partial shading had minimal but positive effect on the crops. More studies are recommended to investigate total roof shading on crop performance